2019
DOI: 10.1039/c9se00293f
|View full text |Cite
|
Sign up to set email alerts
|

Direct use of biomass powder in internal combustion engines

Abstract: A first general assessment of the biomass dust-fuelled engine concept by testing four biomass powders in a single-cylinder engine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…This technology of implementing solid and liquid fuel into the combustion chamber represents most studies in the literature related to solid fuel dust in an internal combustion engine. Recent developments of coal slurry engines have adopted several technical advancements while improving slurry development and injection for higher concentrated slurries (60-65% coal) [ 35]. Some of these developments considered using dry biomass powder in engines instead of coal [33] [35].…”
Section: Characterization Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…This technology of implementing solid and liquid fuel into the combustion chamber represents most studies in the literature related to solid fuel dust in an internal combustion engine. Recent developments of coal slurry engines have adopted several technical advancements while improving slurry development and injection for higher concentrated slurries (60-65% coal) [ 35]. Some of these developments considered using dry biomass powder in engines instead of coal [33] [35].…”
Section: Characterization Methodologymentioning
confidence: 99%
“…The ignition timing control can be assured by both the injection timing and the ignition properties of the injected particles. Most studies in the literature as described above, are limited to the solid particle's combustion in a hot gaseous mixture, and very few consider the interaction of particles with the reactive gas mixture [35]. Based on a gaseous reactive mixture, the quasi-homogeneous species concentration will provide the optimal conditions for the non-production of soot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biofuel is any material used to generate energy from biomass [ 1 ]. Biofuels’ energy source comes from biomass, which stores the sun’s energy as chemical energy [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…5 The energy released can be recovered as a mechanical force and used for high-power generation. Previous studies by our team 4,[6][7][8] have demonstrated that an ultrane lignocellulosic powder, with a median particle size of around 20 mm, is fully compatible with this application 7 but the energy released depends on the physical and chemical properties of the powder. Thus, the production of such powdered fuel is entirely green, provided that the energy required for the milling remains lower than the heating values of the lignocellulosic biomass.…”
Section: Introductionmentioning
confidence: 99%